Susceptibility of bacterioplankton to nutrient enrichment of oligotrophic and ultraoligotrophic lake waters - Beatriz MODENUTTI; Roberto BERTONI; Cristiana CALLIERI; Esteban BALSEIRO (Journal of Limnology, 2008)
We carried out laboratory experiments in one ultraoligotrophic pristine Andean lake (Lake Gutiérrez, Argentina) and in one subalpine lake that is now at the edge of the oligo- to mesotrophic condition (Lake Maggiore, Italy). Lake water was amended with phosphorus (+P), organic carbon (+C), alone or in combination (+CP), to test for short-term changes (48 hours) in bacteria activity and community structure (CARD FISH). Experiments were carried out in spring and summer. Results showed that bacterial production increased in the +CP treatment in both lakes, and in the +P treatment in the ultroligotrophic lake. In both lakes the bacterial activity increased more rapidly in summer (within 24 hours). Bacteria composition changed in both seasons in all the treatments. At the beginning of the experiments the subclass of β-Proteobacteria dominated both lakes, while γ-Proteobacteria showed higher percentage in spring in Lake Maggiore and in summer in Lake Gutiérrez. After incubation, in spring and in particular in the +CP treatment, we observed an increase in the relative importance of γ-Proteobacteria in both lakes, whereas in Lake Maggiore this group declined in the summer experiments following an increase in β-Proteobacteria. All our results indicate the different response of bacterioplankton in systems at the edges of the oligotrophic range.